Characterization of antibiotic resistance and genotyping of Helicobacter pylori isolates in patients with gastroduodenal disease - Nguyen, Thi Khanh Linh; Tran, Thi Nhu Hoa; Phan, Van Bao Thang; Phan, Trung Nam; Bianca, Paglietti; Le, Van An (Tạp chí Y Dược Huế, 2022)
Background: In this study, we assessed the status of antibiotic resistance of H. pylori isolates to antimicrobial agents at Hospital of Hue University of Medicine and Pharmacy in Central Vietnam and identified the underlying molecular mechanisms related to tetracycline and amoxicillin resistance. In addition, the cagA, cagE, cagT, vacA, iceA genotypes of H. pylori strains were investigated to predict clinical outcomes. Materials and methods: H. pylori was successfully cultured in 52 patients with different gastrointestinal disorders at the Hospital of Hue University of Medicine and Pharmacy in Central Vietnam. The minimum inhibitory concentrations (MICs) of five antimicrobials; clarithromycin (CLR), metronidazole (MTZ), levofloxacin (LE), amoxicillin (AMX) and tetracycline (TE) were determined by the E-test method. Genetic determinants of AMX and TE resistance were identified with the polymerase chain reaction (PCR), followed by sequencing and gene analysis. Allelic variants of cagA, cagE, cagT, vacA, iceA were identified by the PCR. Results: The resistance to CLR, MTZ, LE, AMX, and TE were 90.4%, 86.5%, 65.4%, 40.4% and 0%, respectively. Multidrug resistance was observed in 88.5% of the isolates investigated. Several known AMX resistance mutations were identified in PBP1A (A369T, V374L, S543R, T556S, N562Y), whereas a known mutation in 16S rRNA (A926G) was detected in strains with higher MIC level (TE MICs of 0.25 and 0.5 mg/L) . The cagA, cagE and cagT genotypes were found together in 46 isolates (88.5%), vacAs- region genotype in 51 (98.1%, predominantly vacAs1), vacAm- region genotype in all strains studied (vacAm1 - 51.9%, vacAm2 - 40.4%, vacAm1 and vacAm2 - 7.7%), iceA1 in 22 (42.3%) and iceA2 in 20 (38.5%) of strains. The allelic variant vacAs1m1 was prominent (57.4%), and vacAs1m2 (42.6%). Conclusion: Overall, resistance rates to CLR, MTZ, LE and AMX were high in H. pylori from Central Vietnam, except for TE, which serves as a foundation for developing local guidelines for more effective therapeutic strategies. Neither the single genes nor the combination of genes was significantly helpful in predicting the clinical outcome of H. pylori infection in patients in our study.